Blood-Brain Barrier Permeability in Patients With Reversible Cerebral Vasoconstriction Syndrome Assessed With Dynamic Contrast-Enhanced MRI. (2nd November 2021) - Wu, Chia-Hung; Lirng, Jiing-Feng; Wu, Hsiu-Mei; Ling, Yu-Hsiang; Wang, Yen-Feng; Fuh, Jong-Ling; Lin, Chung-Jung; Ling, Kan; Wang, Shuu-Jiun; Chen, Shih-Pin
Abstract : Background and Objectives: Blood-brain barrier (BBB) disruption has been proposed to be important in the pathogenesis of reversible cerebral vasoconstriction syndrome (RCVS), but not all patients present an identifiable macroscopic BBB disruption; that is, visible contrast leakage on contrast-enhanced T2 fluid-attenuated inversion recovery imaging. This study aimed to evaluate microscopic BBB permeability and its dynamic change in patients with RCVS. Methods: This prospective cohort implemented 3T dynamic contrast-enhanced MRI. We measured microscopic BBB permeability by determining the whole-brain and white matter hyperintensity (WMH) K trans values and evaluated the correlation of whole-brain K trans permeability with clinical and vascular measures in transcranial color-coded sonography. Results: In total, 176 patients (363 scans) were analyzed and separated into acute (≦30 days) and remission (≧90 days) groups based on the onset-to-examination time. Whole-brain K trans values were similar between patients with and without macroscopic BBB disruption in either acute or remission stage. The whole-brain K trans was significantly decreased ( p < 0.001) from acute to remission stages. The WMH K trans was significantly higher than mirror references and decreased from acute to remission stages ( p < 0.001). Whole-brain K trans correlated with mean pulsatility index ( r s = 0.5, p = 0.029), mean resistance index ( r s = 0.662, p = 0.002), and distal-to-proximal ratio of resistance index ( r s = 0.801, p < 0.001) of M1 segment of middle cerebral arteries at around 10–15 days after onset. The time-trend curve of whole-brain K trans depicted dynamic changes during disease course, similar to temporal trends of vasoconstrictions and WMH. Discussion: Patients with RCVS presented increased microscopic brain permeability during acute stage, even without discernible macroscopic BBB disruption. The dynamic changes in BBB permeability may be related to impaired cerebral microvascular compliance and WMH formation.